KNOWLEDGE ACQUISITION, ELICITATION, AND MANAGEMENT IN INNOVATIVE FIRMS - Akhmadi, Saltanat; Tsakalerou, Mariza (Procedia Computer Science, 2022)
Knowledge has emerged as a key commodity in smart manufacturing and as a critical resource for innovation and entrepreneurship in Industry 4.0. Innovative firms develop competitive advantages through knowledge exploitation and exploration, whether acquired externally or developed internally. Knowledge management, that is the management of the processes of knowledge creation, sharing and storage, is essential for effective innovation. Software tools to support knowledge management have had limited success in their attempt to address equally well a multitude of sources of knowledge. The data-driven analysis of this paper, however, demonstrates that knowledge acquisition is largely focused within the firm and thus the integrative perspective of considering both internal and external sources of knowledge might be an impediment for the development of appropriate supporting technologies. In this context, the focus should shift to knowledge elicitation and the corresponding development of tools to support it within the firm.
Keywords: Type of access: Open Access; Knowledge management; knowledge acquisition; knowledge elicitation